PERAN ORANG TUA POLA ASUPAN GIZI DALAM MENGEMBANGKAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TKIT ASRI PALEMBANG - Agustinawati, Zulaikha; Fatmawati, Tresna; Rizal, Ahmad Faisal; Darmawati, Junay (Avicenna: Jurnal Ilmiah, 2023)
ABSTRACT Background: Early childhood is a child who has just been born until the age of 6 years. This age is a very determining age in the formation of a child's character and personality. Early age is the age where children experience rapid growth and development. Early age is referred to as golden age. This research is qualitative research using a descriptive approach. The subjects in this research were the school principal, class teachers, parents of students. In the data collection process, researchers used interview methods, observation, data documentation and analysis, data display, data reduction, data conclusion. Meanwhile, the data validity test used in the research is a credibility test using triangulation techniques. The aim of this research is to determine: (1) Nutritional intake of children aged 4-5 years at TKIT ASRI (2) Gross motor development of children aged 4-5 years at TK IT ASRI (3) Methods used to develop gross motor skills of children aged 4 -5 years at TKIT ASRI.From the research results, it can be concluded that: (1) The nutritional intake or food that is often given to children 4-5 years old is healthy food such as 4 healthy 5 perfect food, (2) Children at TKIT ASRI are active children. This can be seen from the characteristics of children whose motor skills are developing according to the Indonesian Ministry of Health (3). The method used to ensure children's motor skills develop well is through gymnastics activities, inviting children to play actively, giving children the freedom to choose games that children like Keywords: Gross Motor Development Age 4-5 years, Nutritional Intake Patterns, Role of Parents